Ex Vivo and In Vivo Assessment of the Penetration of Topically Applied Anthocyanins Utilizing ATR-FTIR/PLS Regression Models and HPLC-PDA-MS - Alexandra Westfall; Gregory T. Sigurdson; Luis E. Rodriguez-Saona; M. Mónica Giusti (MDPI AG, 2020)
Anthocyanins are natural colorants with antioxidant properties, shown to inhibit photoaging reactions and reduce symptoms of some skin diseases. However, little is known about their penetration through the stratum corneum, a prerequisite for bioactivity. The aim was to investigate anthocyanin penetration from lipophilic cosmetic formulations through the skin using a porcine ear model and human volunteers. ATR-FTIR/PLS regression and HPLC-PDA-MS were used to analyze anthocyanin permeation through the stratum corneum. Penetration of all anthocyanins was evident and correlated with molecular weight and hydrophilicity. Lower-molecular-weight (MW) anthocyanins from elderberry (449-581 Da) were more permeable within the skin in both ex vivo and in vivo models (Kp = 2.3-2.4 × 10−4 cm h−1) than the larger anthocyanins (933-1019 Da) from red radish (Kp = 2.0-2.1 × 10−4 cm h−1). Elderberry and red radish anthocyanins were found at all levels of the stratum corneum and at depths for activity as bioactive ingredients for skin health.